FEATURES AND PROBLEMS OF DISCOUNTING IN ASSESSING THE EFFICIENCY OF INNOVATIVE PROJECTS - PYLYPIAK, Oleksandr; BAKAY, Vitaliy (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article provides a comprehensive study of the theoretical and practical aspects of applying the discounting method in assessing the efficiency of innovation projects. The essence of the method, its role in determining the present value of future cash flows, and its place within the system of financial and economic analysis tools are examined. Particular attention is paid to the specific features of using the discounting method in innovation activities, which are characterized by a high level of risk, uncertainty of expected outcomes, and the long duration of the investment cycle.The study addresses the challenges associated with selecting an appropriate discount rate, which is a key factor in accurately evaluating the effectiveness of innovations. It is established that the complexity and ambiguity of determining the discount rate arise from the need to consider macroeconomic conditions, industry-specific risks, cost of capital, inflation expectations, and the inherent characteristics of the innovation process itself. The necessity of improving methodological approaches to discount rate calculation is emphasized, taking into account the peculiarities of the national capital market and the level of development of the innovation environment.The paper identifies and systematizes the key factors influencing the formation of the discount rate and substantiates the relevance of adapting traditional financial models to the conditions of an innovation-driven economy. It is concluded that the effective application of the discounting method enhances the validity of managerial decisions regarding the financing of innovation projects and ensures a balance between expected returns and acceptable levels of risk.
Keywords: value of money; cash flow; discounting; innovation project; investment; business; development